Health benefits of Chlorella vulgaris supplementation: a narrative review - Szada-Borzyszkowski, Kacper; Owczarenko, Konstancja (Quality in Sport, 2026)
Background Dietary supplements are a rapidly growing market, with many of them advertised as remedy for various diseases, or as healthy supplement to the everyday diet. One of these supplements is Chlorella vulgaris, an unicellular alga, which is advertised as a potent remedy for many civilizational diseases. Aim This narrative review aims to summarize current knowledge regarding the supplementation with Chlorella vulgaris, with an emphasis on the clinical, and sports-related use of this supplement, its safety, and efficacy. Materials and methods A narrative review was conducted using PubMed and Google Scholar databases concerning Chlorella vulgaris, with an emphasis on clinical trials, reviews, and meta-analyses. Results and conclusions Evidence suggests that Chlorella vulgaris supplementation may have a beneficial impact on many diseases, such as hypertension, hypercholesterolaemia, or diabetes. Moreover, it might have applications in improving physical endurance, and in the supplementation of micronutrients in some diets. However, some concerns regarding safety, contamination, and heterogeneity of composition still remain. Nevertheless, meta-analyses show, that the evidence for the health benefits is at most moderate, so more research in this area is needed.